Research and Simulation of Key Bending Parameters of Suitable Diameter Oil and Gas Pipeline Cleaning Robots - Dai Yaonan; He Xinhu; Liu Ke; Yang Peiyan; Zhang Jiakang; Zheng Xiaotao; Gong Cheng (Jixie chuandong)
To improve the internal (variable diameter, bending) passage ability of oil and gas pipeline cleaning robots, this study proposes a multi-segment adaptive wheel-type pipeline cleaning robot. The robot adopts a two-segment structural design to reduce the turning radius of the robot, and realizes the self-adaptive movement of different pipe diameters within a certain range through the linear guide rail and wheel leg combination formed by the retractable walking mechanism design. In order to ensure the stability of the cleaning robot during operation in the pipeline, the Adams software is used to simulate the movement process of the pipeline cleaning robot, its motion parameters are analyzed, and the changing rules of the speed and the wheel torque of the robot when passing through the bending pipe and the variable diameter pipe are obtained. The speed of the robot will briefly increase to 1 146.9 mm/s when entering a 90° bend, and then decrease rapidly to 220 mm/s when exiting. In the continuous variable diameter pipe, the speed of the robot is maintained at about 520 mm/s, and the driving motor torque increases to 42.5 N·m with the decrease of the pipe diameter. The simulation data shows the correctness of the theoretical analysis and the rationality of the structural design. The experimental results are consistent with the simulation results, further verifying the rationality of the pipeline cleaning robot design.